Supplying amendments alleviates aluminum toxicity and regulates cadmium accumulation by spinach in strongly acidic soils. (15th December 2022) - Fan, Beibei; Ding, Shuai; Peng, Yutao; Yin, Junhui; Liu, Yanli; Cui, Shihao; Zhou, Xue; Mu, Kangguo; Ru, Shuhua; Chen, Qing
Abstract: Al toxicity and Cd pollution are key limiting factors for agricultural production in the acidic soils in China. The application of amendments is an effective and promising measure for remediating strongly acidic Cd-contaminated soils. However, the information on applying amendments for alleviating Al toxicity and regulating plant Cd accumulation is still rare. Here, oyster shell (OS), red mud (RM), hydroxyapatite (HAP), and biochar (BC) at 30 g kg −1 were investigated for alleviating Al toxicity and decreasing Cd accumulation in spinach plants. The results showed that four amendments significantly increased soil pH, and reduced soil exchangeable Al 3+ and DTPA-Cd, promoted spinach growth ( P < 0.05). Al(OH)3 0 and Al-HA were the main forms of active Al in soil. The BC and OS were more effective to alleviate Al toxicity but significantly ( P < 0.05) increased Cd accumulation in spinach. RM and HAP effectively reduced the uptake of Cd by spinach plants as well as alleviated Al toxicity ( P < 0.05). Bivariate correlation analysis and the partial least squares path modeling analysis indicated that soil exchangeable Al 3+ was the main limiting factor for biomass production. Our study demonstrated that HAP could significantly alleviate Al toxicity, promote spinach growth, and decrease Cd accumulation in strongly acidic Cd-contaminated soils. Besides, OS and BC effectively alleviated soil Al toxicity leading to promoting the growth of spinach. Compared with CK, RM treatment significantly reduced soil Cd bioavailability (61.2%) and decreased Cd concentration and uptake of spinach plants by 90.0% and 50.7%. These results indicated that RM could be used as an efficient amendment in Cd contaminated. Graphical abstract: Image 1 Highlights: Amendments reduced exchangeable Al 3+ and raised humic acid Al to alleviate Al toxicity. Oyster shell and biochar reduced soil exchangeable Al 3+ by 100%. Hydroxyapatite alleviated Al toxicity by increasing of Al(OH)3 0 and humic acid Al. Oyster shell and biochar had presented a better effect on promoting growth. Red mud and hydroxyapatite significantly reduced Cd accumulation in spinach plants.